2008
DOI: 10.1016/j.ejheart.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose erythropoietin improves cardiac function in experimental heart failure without increasing haematocrit

Abstract: Background: Erythropoietin (EPO) may improve cardiac function and induce neovascularisation in experimental models of chronic heart failure (CHF). However, the increased haematocrit associated with EPO treatment might exert concomitant deleterious effects. Aim: To investigate the haematocrit independent effects of EPO on cardiac function. Methods and results: Rats underwent permanent coronary artery ligation to induce myocardial infarction (MI) or sham surgery. Three weeks after MI, rats were randomly allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 34 publications
3
55
1
1
Order By: Relevance
“…In this regard, Hamid et al (17) found that EPO treatment improved the myocardial performance in doxorubicin-induced cardiomyopathy, which was associated with an increase in HCT levels in their EPO control rats (23). In another study, it has been found that low-dose of EPO improves cardiac function in experimental heart failure without increasing HCT levels; however, some of the beneficial effects were less pronounced in the "low-dose group" than "high dose group" in this study, which might indicate that some of the beneficial effects are related to increased HCT levels and consequently increased oxygen delivery (22). Thus the optimal dose and timing of EPO treatment during chemotherapy are very important and still need to be defined.…”
Section: Discussioncontrasting
confidence: 49%
“…In this regard, Hamid et al (17) found that EPO treatment improved the myocardial performance in doxorubicin-induced cardiomyopathy, which was associated with an increase in HCT levels in their EPO control rats (23). In another study, it has been found that low-dose of EPO improves cardiac function in experimental heart failure without increasing HCT levels; however, some of the beneficial effects were less pronounced in the "low-dose group" than "high dose group" in this study, which might indicate that some of the beneficial effects are related to increased HCT levels and consequently increased oxygen delivery (22). Thus the optimal dose and timing of EPO treatment during chemotherapy are very important and still need to be defined.…”
Section: Discussioncontrasting
confidence: 49%
“…Lipsic et al compared these effects of low-dose EPO (0.4 μg/kg for 3 weeks) to a high EPO dose (40 μg/kg for 3 weeks, 100-fold higher), with previously established effects on cardiac function in post-MI heart failure of rats. 21 Similar to high-dose EPO, low-dose EPO induced neovascularization and attenuated the unfavorable switch to slow β-MHC isoforms. However, in contrast to high-dose EPO, LVEDP was not significantly attenuated in the low-dose group compared to the untreated MI.…”
Section: Discussionmentioning
confidence: 99%
“…Lipsic et al reported that low dose (0.4 μg/kg) EPO analogue darbepoetin-alfa improved cardiac function and induced neovascularization in post-MI heart failure of rats, the effect of which was similar to higher dose (40 μg/kg) administration. 21 Lower doses of EPO was shown to confer vascular and tissue protection in the kidney, 22 and its safety is approved by the general use in autologous blood collection. 23 Therefore, our pilot study was designed to investigate the effects of short-term low-dose EPO administration on the neointimal hyperplasia in PCI-treated coronary arteries and infarct size (primary endpoints) and cardiac function (second endpoint) in the patients with ST-elevated AMI.…”
mentioning
confidence: 99%
“…20 -23 These effects are seen even when erythropoietin is administered in low doses that do not increase hematocrit. 24 These extrahematopoietic effects may be useful in HF and may prevent cardiac function loss after myocardial infarction. Presently, a randomized multicenter trial is evaluating the effect of a single bolus of erythropoietin administered after a first acute myocardial infarction on left ventricular function.…”
Section: Discussionmentioning
confidence: 99%